Tracing the Instances of Plea Bargaining in the Lithuanian Criminal Justice System - Garbatavičiūtė, Simona (Teisė, 2018)
This Article aims to overview procedural grounds in the Lithuanian criminal justice system that relate to the concepts of simplified and negotiated justice, in particular to the concept of plea bargaining. Specifically, the research seeks to examine the procedures of simplified examination of evidence in court, accelerated proceedings and the procedure of penal order as foreseen in the Code of Criminal Procedure of the Republic of Lithuania (hereinafter referred to as the CCP). This research aims to highlight similarities between the aforementioned procedures and the concept of plea bargaining.
Keywords: nėra